Was Calypso Able to Make Odysseus Immortal? - Bartol, Krystyna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
The article, focusing primarily on the Odyssey 5. 135–6, offers a set of remarks designed to foreground the qualities that make the Calypso episode not only interesting as an example of how the epic poet exploits traditional themes and phrases, but exciting as a story of a man’s desire.